Methylated DNA is over-represented in whole-genome bisulfite sequencing data - Ji, Lexiang; Sasaki, Takahiko; Sun, Xiaoxiao; Ma, Ping; Lewis, Zachary A.; Schmitz, Robert J. (Frontiers in Genetics, 2014)
The development of whole-genome bisulfite sequencing (WGBS) has led to a number of exciting discoveries about the role of DNA methylation leading to a plethora of novel testable hypotheses. Methods for constructing sodium bisulfite-converted and amplified libraries have recently advanced to the point that the bottleneck for experiments that use WGBS has shifted to data analysis and interpretation. Here we present empirical evidence for an over-representation of reads from methylated DNA in WGBS. This enrichment for methylated DNA is exacerbated by higher cycles of PCR and is influenced by the type of uracil-insensitive DNA polymerase used for amplifying the sequencing library. Future efforts to computationally correct for this enrichment bias will be essential to increasing the accuracy of determining methylation levels for individual cytosines. It is especially critical for studies that seek to accurately quantify DNA methylation levels in populations that may segregate for allelic DNA methylation states.